Charge-Coupled device based on optical tomography system for monitoring multiphase flow - Jamaludin J.; Rahim R.A.; Rahiman M.H.F.; Muji S.Z.M.; Rohani J.M.; Wahab Y.A. (Penerbit UTHM, 2024)
Vol. 9 No. 3 (2017)